Prison theatre and the global crisis of incarceration - Lucas, Ashley (Critical companions., 2020)
"Obscured behind concrete and razor wire, the lives of the incarcerated remain hidden from public view. Inside the walls, imprisoned people all over the world stage theatrical productions that enable them to assert their humanity and capabilities. Prison Theatre and the Global Crisis in Incarceration examines performances within prisons across the globe, offering a uniquely international account and exploration of prison theatre. By discussing a range of performance practices tied to incarceration, this book looks at the ways in which arts practitioners and imprisoned people use theatre as a means to build communities, attain professional skills, create social change, and maintain hope. Ashley Lucas's writing offers a distinctive blend of storytelling, performance analysis, travelogue, and personal experience as the child of an incarcerated father. Distinct examples of theatre performed in prisons are explored throughout the main text and also in a section of Critical Perspectives by international scholars and practitioners considering the philosophical underpinnings of this work and its impact on audiences and actors. The vivid descriptions of performances make this volume a terrific resource for students, facilitators and teachers of prison theatre"-- Provided by publisher.